2008
DOI: 10.1104/pp.108.123703
|View full text |Cite
|
Sign up to set email alerts
|

SUGAR-DEPENDENT6 Encodes a Mitochondrial Flavin Adenine Dinucleotide-Dependent Glycerol-3-P Dehydrogenase, Which Is Required for Glycerol Catabolism and Postgerminative Seedling Growth in Arabidopsis

Abstract: The aim of this study was to clone and characterize the SUGAR-DEPENDENT6 (SDP6) gene, which is essential for postgerminative growth in Arabidopsis (Arabidopsis thaliana). Mutant alleles of sdp6 were able to break down triacylglycerol following seed germination but failed to accumulate soluble sugars, suggesting that they had a defect in gluconeogenesis. Mapbased cloning of SDP6 revealed that it encodes a mitochondrial flavin adenine dinucleotide (FAD)-dependent glycerol-3-P (G3P) dehydrogenase:ubiquinone oxido… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 35 publications
5
40
0
1
Order By: Relevance
“…The suppression of photosynthesis and the regulation of glycerol and mitochondrial metabolism during O 3 stress may dissipate excess energy to avoid the formation of oxidative radicals (Hoefnagel et al, 1998), combining fast NAD + recycling with the maintenance of central metabolism and growth (Dizengremel et al, , 2012. This hypothesis is supported by previous studies on the physiological functions of glycerol metabolism in NADH/NAD + homeostasis (Shen et al, 2006;Quettier et al, 2008), osmotic stress responses (Biela et al, 1999;Eastmond, 2004;Chen et al, 2011;Geijer et al, 2012), and plant development (Hu et al, 2014). These pathways were redirected in the sequential treatment, during which glycerolipid resources may have been reallocated toward JA signaling and defense against herbivores (Turner et al, 2002;Kachroo et al, 2004;Havko et al, 2016).…”
Section: O 3 and Herbivory Affect Central Metabolism In Opposite Wayssupporting
confidence: 74%
See 1 more Smart Citation
“…The suppression of photosynthesis and the regulation of glycerol and mitochondrial metabolism during O 3 stress may dissipate excess energy to avoid the formation of oxidative radicals (Hoefnagel et al, 1998), combining fast NAD + recycling with the maintenance of central metabolism and growth (Dizengremel et al, , 2012. This hypothesis is supported by previous studies on the physiological functions of glycerol metabolism in NADH/NAD + homeostasis (Shen et al, 2006;Quettier et al, 2008), osmotic stress responses (Biela et al, 1999;Eastmond, 2004;Chen et al, 2011;Geijer et al, 2012), and plant development (Hu et al, 2014). These pathways were redirected in the sequential treatment, during which glycerolipid resources may have been reallocated toward JA signaling and defense against herbivores (Turner et al, 2002;Kachroo et al, 2004;Havko et al, 2016).…”
Section: O 3 and Herbivory Affect Central Metabolism In Opposite Wayssupporting
confidence: 74%
“…Pathway visualization in KEGG/KaPPAView4 ( Fig. 6F) showed that GPDHc1 and SDP6 (located in the cytosol and on the mitochondrial membrane, respectively) constitute the G3P shuttle that is responsible for transporting reducing equivalents to the mitochondrial ETC via dihydroxyacetone phosphate recycling (Shen et al, 2003(Shen et al, , 2006Quettier et al, 2008).…”
Section: Responses Relative To Energy and Glycerol Metabolic Networkmentioning
confidence: 99%
“…Figure 3 shows the hydrolysis of seed triacylglycerol to free fatty acids and glycerol by the action of one or more lipases. The glycerol formed is phosphorylated and subjected to glycogenesis after its conversion to dihydroxyacetone phosphate (DHAP) (Quettier et al 2008). The free fatty acids are transported into the peroxisome, where they are activated into acytil-COA and initiate β-oxidation.…”
Section: Seed Lipasesmentioning
confidence: 99%
“…Briefly, TAGs are hydrolysed to free fatty acids and glycerol by TAG lipases. The glycerol is phosphorylated and enters gluconeogenesis after its conversion to dihydroxyacetone phosphate [4]. The free fatty acids are transported to the glyoxysome where they are activated to acyl-CoAs and enter the ß-oxidation spiral.…”
Section: Introductionmentioning
confidence: 99%